Analisis Implikatur Percakapan Dalam Novel Si Anak Spesial Karya Tere Liye dan Pemanfaatannya Sebagai Bahan Ajar di Sekolah Menengah Atas - Maulana, Nanang; Susanti, Susi (GERAM: Gerakan Aktif Menulis, 2022)
This study analyzes conversational implicatures in Tere Liye's The Special Child novel and its use as teaching material in high school. This study aims to describe common conversational implicatures and their use as teaching materials in high school. The author's reason for conducting this research is to understand the novel not only by reading it as a whole but also to interpret the implicit messages contained in the novel by understanding the conversational implicature, the context of the conversation, and the form of the conversation. This study uses a qualitative descriptive research method. The techniques used in data collection are reading strategies and note-taking techniques. The data source of this research is the data source obtained only based on the novel The Special Child by Tere Liye, which is analyzed using Nadar's theory. Data analysis uses three stages: data reduction, presentation, and conclusion. The study indicates that conversational implicatures in the novel Si Anak Special by Tere Liye found as many as 25 general conversations. 3.9 about analyzing the content and language of the novel. With the learning objectives, students can analyze the content and language of Tere Liye's The Special Child novel, which contains conversational implicatures